2006
DOI: 10.1097/01.sla.0000183349.16877.84
|View full text |Cite
|
Sign up to set email alerts
|

Gut Hormone Profiles Following Bariatric Surgery Favor an Anorectic State, Facilitate Weight Loss, and Improve Metabolic Parameters

Abstract: Following RYGB and JIB, a pleiotropic endocrine response may contribute to the improved glycemic control, appetite reduction, and long-term changes in body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
652
4
38

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 898 publications
(756 citation statements)
references
References 44 publications
50
652
4
38
Order By: Relevance
“…Despite equivalent weight loss, the post-RYGB group showed markedly better glucose tolerance by oral glucose tolerance testing than did the post-AGB group. Similarly, leRoux et al 27 observed better glucose tolerance in people following RYGB than after equivalent weight loss from AGB, and the estimated insulin sensitivity of the post-RYGB group was equivalent to that of lean counterparts, despite a significantly higher BMI in the post-surgical patients. Korner et al 28 also observed better glucose tolerance following a standardized test meal in a cross-sectional analysis of patients who had undergone RYGB compared with AGB, with equal postoperative BMI values.…”
Section: Mechanisms Of Diabetes Improvement Following Bariatric Surgerymentioning
confidence: 81%
See 1 more Smart Citation
“…Despite equivalent weight loss, the post-RYGB group showed markedly better glucose tolerance by oral glucose tolerance testing than did the post-AGB group. Similarly, leRoux et al 27 observed better glucose tolerance in people following RYGB than after equivalent weight loss from AGB, and the estimated insulin sensitivity of the post-RYGB group was equivalent to that of lean counterparts, despite a significantly higher BMI in the post-surgical patients. Korner et al 28 also observed better glucose tolerance following a standardized test meal in a cross-sectional analysis of patients who had undergone RYGB compared with AGB, with equal postoperative BMI values.…”
Section: Mechanisms Of Diabetes Improvement Following Bariatric Surgerymentioning
confidence: 81%
“…Nevertheless, recent studies clearly show that meal-stimulated secretion of GLP-1 and other L-cell peptides such as peptide YY is, indeed, substantially and durably increased after RYGB, whereas this does not occur after AGB. 27,28,40,41 Consistent with elevated postprandial GLP-1 secretion, post-RYGB patients display an increased incretin effect. 25,40 As GLP-1 not only enhances insulin secretion but can also increase proliferation and decrease apoptosis of b cells, 39 it is a candidate mediator of the increase in b-cell mass that is claimed by some investigators to accompany post-RYGB hyperinsulinemic hypoglycemia.…”
Section: The Lower Intestinal Hypothesismentioning
confidence: 99%
“…Six months after vertical banded gastroplasty, fasting plasma GLP-1 concentrations did not change significantly, but the area under the curve during an oral glucose tolerance test strikingly increased [48]. However, in another study involving patients submitted to gastric banding, GLP-1 levels after a test meal were similar to body-weight-matched obese controls [15]. It is pertinent to add that fasting levels of PYY and GLP-1 are generally low, and changes in these anorexigenic signals occur in the post-prandial period.…”
Section: Discussionmentioning
confidence: 91%
“…In humans, fasting and post-prandial plasma levels of PYY increase progressively 6 and 12 months after vertical banded gastroplasty surgery [46]. Some authors have found that the PYY area under the curve after a test meal was also superior in obese patients submitted to gastric banding when compared weight-matched obese controls [15], although in another similar study, this was not found to be the case [47]. Six months after vertical banded gastroplasty, fasting plasma GLP-1 concentrations did not change significantly, but the area under the curve during an oral glucose tolerance test strikingly increased [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation